Reduced dementia incidence after varicella zoster vaccination in Wales 2013–2020 - Christian Schnier; Janet Janbek; Richard Lathe; Jürgen Haas (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Chronic infection with herpes viruses is a potential contributing factor to the development of dementia. The introduction of nationwide shingles (varicella zoster) vaccination in Wales might therefore be associated with reduced incident dementia. Methods We analyzed the association of shingles vaccination with incident dementia in Wales between 2013 and 2020 using retrospectively collected national health data. Results Vaccinated individuals were at reduced risk of dementia (adjusted hazard ratio: 0.72; 95% confidence interval: 0.69 to 0.75). The association was not modified by a reduction in shingles diagnosis and was stronger for vascular dementia than for Alzheimer's disease. Vaccination was also associated with a reduction in several other diseases and all‐cause mortality. Discussion Our study shows a clear association of shingles vaccination with reduced dementia, consistent with other observational cohort studies. The association may reflect selection bias with people choosing to be vaccinated having a higher healthy life expectancy.